Improving irrigation performance through the use of management information systems: the case of Mahi Kadana, Gujarat, India - Murray-Rust, Hammond; Gulati, O.T.; Sakthivadivel, Ramaswamy; Prajapati, V.B.; Shukla, P.L. (International Irrigation Management Institute, 1994)
This paper describes the development and implementation of a management information system for the Mahi Kadana irrigation project in Gujarat , India. It describes the sequential process of modification of field -level data collection procedures by low level staff of the Gujarat Irrigation department, the development of improved methods for communicating these field-level data in a timely and efficient manner to managers at section and subdivision levels, and the development of a data processing package that transfers field-level data into information to be used by managers in improving performance into the future. The second part of the paper demonstrates how the output from the computer can be used to develop performance reports.